Two-particle azimuthal correlations as a probe of collective behaviour in deep inelastic ep scattering at HERA - Abt, Iris; Adamczyk, L.; Aggarwal, R.; Aushev, V.; Behnke, O.; Behrens, U.; Bertolin, A.; Bloch, I.; Brock, I.; Brook, N. H.; Brugnera, R.; Bruni, A.; et al. (Journal of high energy physics, 2020)
Two-particle azimuthal correlations have been measured in neutral current deep inelastic ep scattering with virtuality Q(2)> 5 GeV2 at a centre-of-mass energy root s = 318 GeV recorded with the ZEUS detector at HERA. The correlations of charged particles have been measured in the range of laboratory pseudorapidity -1.5 < eta < 2.0 and transverse momentum 0.1 < p(T)< 5.0 GeV and event multiplicities N-ch up to six times larger than the average < N-ch >approximate to 5. The two-particle correlations have been measured in terms of the angular observables c(n{2})=<< cosn Delta phi >>, where n is between 1 and 4 and phi is the relative azimuthal angle between the two particles. Comparisons with available models of deep inelastic scattering, which are tuned to reproduce inclusive particle production, suggest that the measured two-particle correlations are dominated by contributions from multijet production. The correlations observed here do not indicate the kind of collective behaviour recently observed at the highest RHIC and LHC energies in high-multiplicity hadronic collisions.